Air‐sea gas transfer rate for the Southern Ocean inferred from 222Rn concentrations in maritime air and a global atmospheric transport model. Issue 14 (24th July 2013) - Taguchi, S.; Tasaka, S.; Matsubara, M.; Osada, K.; Yokoi, T.; Yamanouchi, T.
Abstract : [1] Measurements of atmospheric 222 Rn activity were made on board the icebreaker Shirase during the summers of 2004 and 2005, between 32°S and 69°S. Global atmospheric 3‐D model calculation of 222 Rn were conducted using hypothetical emissions from ocean and land including the Antarctic continent. Oceanic emissions were estimated based on wind speed parameterizations from the literature and by using radium in the ocean as a surrogate of surface radon concentrations. Modeled results suggest that a significant part of the measured activities originate from a release from the ocean and the Antarctic continent. Based on regression analysis, we investigated the power‐law description of wind speed that best fits the measured concentrations. The correlation, root mean square errors, and emission from the Antarctic continent suggest that a 3.5 power law best fits the measured activities. However, the merit of this choice is not statistically significant, and the proportionality factor that scales a wind speed description with a flux depends on the dilution of radon in the mixing layer of the ocean. These weaknesses, therefore, pose a limitation for the application of the current parameterization to the other gases. Key Points: Atmospheric Rn over Antarctic Ocean came from the ocean and the Antarctic A 3.5 power law of hourly wind best fitted the measured concentrations Magnitude of the flux depends on the dilution of Rn in the mixing layer